Non-steroidal Anti-inflammatory Drug Consumption in a Multi-Stage and a 24-h Mountain Bike Competition - Chlíbková, Daniela; Ronzhina, Marina; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2018)
Purpose: Excessive or inappropriate non-steroidal anti-inflammatory drug (NSAID) use during ultra-endurance events could cause potential risk to athletes’ health. Reports on NSAID consumption in mountain bikers or ultra-mountain bikers are scarce. Therefore, the aim of this study was to investigate the prevalence of NSAID consumption immediately before, during and immediately after a mountain bike (MTB) race and to compare NSAID consumption in two different MTB competitions. Methods: This observational study took place at a three-stage MTB race (SMTB) (n=63) and at a 24-hour MTB race (24MTB) (n=68), both held in the Czech Republic in 2017. NSAID consumption was evaluated via self-reported electronic questionnaires. Results: Of all finishers (n=131), fourteen (10%) consumed NSAID at least once during the competition day (immediately before, during or immediately after the race). The number of NSAID consumers was the same in both competitions. Nevertheless, only three athletes (2%), all of them from the 24MTB, consumed NSAID during the race and 5% of all mountain bikers reported consumption after the race. In contrast to the SMTB, the intake reported by the 24MTB participants was quite homogeneous in terms of the timing of NSAID consumption. The NSAID users were older (p=0.043) than the non-users. Ibuprofen was most commonly used by 79% of all consumers. Conclusions: The prevalence of NSAID use was higher in the older participants and seems to be lower in comparison with results from studies about runners, ultra-runners and triathletes suggesting that it is determined by the discipline (i.e. cycling). On the other hand, the timing of NSAID consumption was probably affected by the competition character (e.g. MTBS or 24MTB). Future studies should focus on a larger sample size of cyclists from various disciplines.